Expanded CAG Repeats in ATXN1, ATXN2, ATXN3, and HTT in the 1000 Genomes Project. Issue 2 (7th November 2020) - Akçimen, Fulya; Ross, Jay P.; Liao, Calwing; Spiegelman, Dan; Dion, Patrick A.; Rouleau, Guy A.
ABSTRACT: Background: Spinocerebellar ataxia types 1, 2, 3 and Huntington disease are neurodegenerative disorders caused by expanded CAG repeats. Methods: We performed an in‐silico analysis of CAG repeats in ATXN1, ATXN2, ATXN3, and HTT using 30× whole‐=genome sequencing data of 2504 samples from the 1000 Genomes Project. Results: Seven HTT ‐positive, 3 ATXN2 ‐positive, 1 ATXN3 ‐positive, and 6 possibly ATXN1 ‐positive samples were identified. No correlation was found between the repeat sizes of the different genes. The distribution of CAG alleles varied by ethnicity. Conclusion: Our results suggest that there may be asymptomatic small expanded repeats in almost 0.5% of these populations. © 2020 International Parkinson and Movement Disorder Society